Pariwisata Halal di Aceh: Analisis Kepatuhan Pelaku Usaha Terhadap Fatwa MPU Nomor 2 Tahun 2022 di Dataran Tinggi Gayo - Pinta Febriana; Safwan Safwan (JURNAL RECHTENS, 2026)
This study examines the implementation of MPU Aceh Fatwa No. 2 of 2022 concerning Halal Tourism in the Gayo Highlands as a legal instrument regulating tourism activities based on Islamic principles. The study aims to analyze the conformity of halal tourism practices with the provisions of the fatwa and the level of compliance among tourism business actors. This research employs an empirical legal method using statutory and sociological approaches through interviews, observations, and documentation involving tourism business actors, destination managers, and related institutions. The findings reveal that the implementation of halal tourism principles has reached approximately 60–70%, particularly in the provision of halal food, prayer facilities, and Islamic services. However, the implementation remains suboptimal due to limited facilities, weak supervision of tourist activities, and the partial understanding of halal tourism among business actors. The study concludes that MPU Aceh Fatwa No. 2 of 2022 has not been fully effective as a social engineering instrument; therefore, stronger regulations, supervision, and socialization for tourism business actors are necessary